g-C3N4 Modified by meso-Tetrahydroxyphenylchlorin for Photocatalytic Hydrogen Evolution Under Visible/Near-Infrared Light - Liu, Yanfei; Ma, Zhen (Frontiers in Chemistry, 2020)
A new photocatalyst denoted as mTHPC/pCN was prepared by modifying protonated graphitic carbon nitride (pCN) by meso-tetrahydroxyphenylchlorin (mTHPC). Relevant samples were characterized via various methods including zeta potential measurements, X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), N2 adsorption-desorption, transmission electron microscopy (TEM), ultraviolet-visible-near-infrared spectroscopy (UV-VIS-NIR), electrochemical impedance spectroscopy (EIS), photocurrent response measurements, electron spin resonance spectroscopy (ESR), and phosphorescence spectroscopy. Compared with protonated graphitic carbon nitride (pCN), mTHPC/pCN shows enhanced absorption in the visible and near-infrared regions, and thus higher photocatalytic activity in hydrogen evolution. A possible mechanism for mTHPC/pCN is proposed.